Physico-chemical properties of spray dried powders from two varieties of amaranth (Amaranthus viridis) - M. A., Siti Faridah; Tan, L. Y.; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
The increasing demand for natural colorant had led to the search for new sources of various colour pigments. Amaranthus viridis which is locally known as ‘bayam hijau’ is found in abundant in the Malaysian market and hence this green leafy plant has the potential to become a new source of colorant due to its significant content of chlorophylls. A study was, therefore, carried out to determine the chlorophyll content of 5 local green leafy vegetables including two species of green amaranth (round and oval leaves). The effect of water extraction with and without prior blanching on the yield of amaranth powder, chlorophyll content, antioxidant activity and powder properties of the spray-dried amaranth of both varieties were evaluated. The extracts were microencapsulated using 20% maltodextrin of DE 10 at an inlet temperature of 150 ± 50C and a feed rate of 300 mL/h. The highest yield (69.8%) of spray-dried powder was obtained from the extract of unblanched amaranth round leaves. In addition, this powder possessed the highest 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and showed the highest chlorophyll retention which was 1536.8 μM Trolox Equivalent (TE)/g and 95.6%, respectively. It was also found that this powder had the highest bulk density and solubility compared to the powder from unblanched amaranth oval leaves which were 0.51 g/mL and 77.9%, respectively. However, the spray-dried powder from unblanched amaranth oval leaves appeared to be more green than the powder from unblanched round leaves with L* value of 76.7, a* value of -3.8 and b* value of 14.0. The chlorophyll content of the former powder was higher than that of the latter powder which was 8.87 mg/100 g. The findings of this study indicated that blanching did not improve the antioxidant activity and colour of spray-dried amaranth powder. Meanwhile, spray-dried powder from unblanched amaranth round leaves had better physico-chemical properties compared to that from unblanched oval leaves except for its chlorophyll content and green colour.